Estudo sobre o entupimento na descarga de silos de produto acabado em empresa de alimentos para cães e gatos - Silva, Rosimeire Lemos da (Universidade Federal de São Carlos, 2022)
Industries producing food for dogs and cats, belonging to the pet sector food, are extremely relevant to the Brazilian economy and have shown growth year after year, but despite this positive scenario, factors such as the increase in the value of raw materials and the general cost of living in Brazil, in addition to the increase in the number of competitors, make them need increasingly efficient processes to maintain their profitability. The clogging of finished product silos, which happens when the unloading of the product suffers a partial or total stoppage, it is one of the causes of considerable loss efficiency in dry feed industries and in other sectors dealing with solids granular or powdery, being also a critical problem from the point of view of safety. The profile of the flow of stored products, the geometry of the silos and environmental factors, such as temperature and humidity, are directly related to the occurrence of clogging. Due to the diversity of products made in the plant that was subject to of study in the present work, implying in the existence of several profiles of flow of flow, and the impossibility of abruptly changing the geometry of the installed silos, it was decided to analyze the influence of environmental factors, where it is concluded that the increase in temperature is directly related to the increase in the occurrence of clogging due to to the coating properties of kibbles.
Study on clogging in the discharge of silos in a dog and cat food industry
Keywords: Descarga gravitacional; Ração animal; Obstrução; Kibble; Clogging; ENGENHARIAS::ENGENHARIA QUIMICA